2007
DOI: 10.1152/physiolgenomics.00027.2006
|View full text |Cite
|
Sign up to set email alerts
|

Congenic strains confirm aerobic running capacity quantitative trait loci on rat chromosome 16 and identify possible intermediate phenotypes

Abstract: December 19, 2006; doi:10.1152/physiolgenomics.00027.2006.-We previously identified two inbred rat strains divergent for treadmill aerobic running capacity (ARC), the low-performing Copenhagen (COP) and the high-performing DA rats, and used an F2(COPϫDA) population to identify ARC quantitative trait loci (QTLs) on rat chromosome 16 (RNO16) and the proximal portion of rat chromosome 3 (RNO3). Two congenic rat strains were bred to further investigate these ARC QTLs by introgressing RNO16 and the proximal portio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In a follow-up study, chromosomes 16 and 3 of DA rats were introgressed into the genetic background of COP rats. The DA chromosome 16 congenic COP rats had significantly greater aerobic running capacity than the COP rats (366). Using a similar paradigm, Lightfoot and colleagues intercrossed inbred mouse strains displaying high and low maximal exercise endurance capacity (166).…”
Section: Genetics Cardiorespiratory Endurance and Muscle Strengthmentioning
confidence: 87%
“…In a follow-up study, chromosomes 16 and 3 of DA rats were introgressed into the genetic background of COP rats. The DA chromosome 16 congenic COP rats had significantly greater aerobic running capacity than the COP rats (366). Using a similar paradigm, Lightfoot and colleagues intercrossed inbred mouse strains displaying high and low maximal exercise endurance capacity (166).…”
Section: Genetics Cardiorespiratory Endurance and Muscle Strengthmentioning
confidence: 87%
“…Over the past several years, studies examining both maximal endurance phenotypes and physical activity phenotypes in rodents have been reported in an effort to assess the genetic/biological factors involved in the regulation of these exercise behaviors [14, 18, 22, 23, 26, 27, 31, 32, 36, 40]. Given the relative consistency of these measures of exercise behaviors in humans (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…VO 2 max tests) and in smaller reported cohorts of mice, all of which assessed repeatability of VO 2 max measurements [6, 17, 31], it has been natural to assume that these measures were repeatable in mice. In addition, given the fact that VO 2 max is a good predictor of exercise endurance in humans [5, 11], and has been shown repeatable, the assumption could be made that maximal endurance tests used to assess endurance in rodents [4, 18, 24, 40] would also be repeatable. Our finding of within strain consistency of overall endurance in different cohorts of mice over a six year period (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ways et al, 2007). Studies in rodents (see also Kumar et al, 2010) have identified a number of quantitative trait loci (QTL) that account for a statistically significant fraction of the variation in experimentally created mapping populations (e.g.…”
Section: Genetic Basis Of Variation In Physical Activity and Related mentioning
confidence: 99%